(untitled) (Educational Dimension, 2023)
This article focuses on the generalization of foreign experiences in implementing STEM education and places particular emphasis on the areas of professional training for future teachers of STEM disciplines. By conducting bibliometric analyses of sources from Scopus (93 sources) and Web of Science (42 sources) scientometric databases, four clusters were identified using VOSviewer: 1) STEM education and training; 2) teacher training and primary education; 3) surveys on STEM education; and 4) e-learning and computational thinking in the training of future teachers of STEM disciplines. The research results demonstrate the importance and relevance of STEM education in various fields, and the leading role of the cluster "STEM education and training" has been determined based on the number and strength of links within the network of keyword links of sources on professional training of future STEM teachers. The discussion of the research findings highlights views on the prospects for STEM development in different countries. It is determined that: a) the professional training and social status of teachers are strategically important links in STEM education; b) teachers of "traditional" STEM disciplines (mathematics and natural sciences) require an increased level of knowledge in the field of information technology, particularly through the integration of programming as a component of STEM education; and c) social virtual reality platforms, hyperrealistic modeling, virtual laboratories, educational robotics, augmented, and mixed reality technologies are recommended to increase the motivation of pupils and students to study STEM disciplines.